Assessing career progression among female health workers in the Ghana health service in the Kumasi Metropolis. - DUODU, SANDRA (KNUST, 2025)
A Thesis Submitted To The Department Of Human Resource And Organizational Development In Partial Fulfilment Of The Requirements For The Degree Of Master Of Business Administration (Hrm Option)